Pemenuhan Hak Konstitusional Warga Negara Indonesia Beragama Yahudi Sebagai Penduduk yang Agamanya Belum Diakui Sebagai Agama Berdasarkan Ketentuan Peraturan Perundang – Undangan - Herri Bona Saut Simatupang; Manotar Tampubolon; John Pieries (Syntax Idea)
This research explores the status and challenges faced by the Jewish community in Indonesia, particularly regarding the non-recognition of their religion by the government. The study aims to understand the impact of religious non-recognition on the constitutional rights guaranteed by the 1945 Constitution of the Republic of Indonesia for Jewish believers. Using a normative legal approach and literature study method, this research analyzes various laws, regulations, and other relevant legal documents, as well as traces the history of legal institutions to understand its context. The findings reveal that although the Jewish community has been present in Indonesia since the era of Srivijaya, Judaism is not officially recognized by the government. As a result, Jewish believers face challenges in practicing their faith, including difficulties in establishing places of worship and obtaining legal protection. Nevertheless, they remain active in practicing their faith, making efforts such as establishing synagogues and communicating with Jewish communities abroad.